Autoimmune Encephalitis with Autoantibodies to NMDAR1 Following Herpes Encephalitis in Children and Adolescents - Quade, Annegret; Rostasy, Kevin; Wickstrom, Ronny; Aydin, Omer Faruk; Sartori, Stefano; Nosadini, Margherita; Haeusler, Martin (Georg Thieme Verlag KG, 2023)
Herpes simplex virus (HSV) type 1 is a frequent pathogen causing infectious encephalitis (HSVE). Early treatment with intravenous acyclovir has led to a significant decrease in mortality. However, especially in children, deterioration during or after HSVE may occur without any evidence of HSV reactivation or improvement following repeated antiviral therapy. Here, we report 15 patients (age range 3 months to 15 years) who suffered from autoimmune encephalitis with autoantibodies to NMDAR1 following Herpes encephalitis, presenting with movement abnormalities (young children) or neuropsychiatric symptoms (older children) as major complaints, respectively. The diagnosis was based on positive cerebrospinal fluid (CSF) and/or serum anti-NMDAR-antibodies with two children showing only positive CSF antibody findings. The time lag between first symptoms and diagnosis of autoimmune encephalitis was significantly longer than between first symptoms and diagnosis of HSVE ( p < 0.01). All patients improved during immunosuppressive treatment, during which plasmapheresis or rituximab treatments were applied in 11 patients, irrespective of their age. Despite immunotherapy, no patients relapsed with HSVE. Early diagnosis and treatment of autoimmune encephalitis after HSVE may be associated with a better outcome so that high clinical awareness and routine testing for anti-NMDAR-antibodies after HSVE seems advisable. If autoimmune encephalitis is suspected, antibody testing should also be performed on CSF if negative in serum.
Korinthenberg, Rudolf/0000-0002-4638-3460; Aydin, Ömer Faruk/0000-0003-2089-7508; Knierim, Ellen/0000-0002-4769-7322;
Keywords: Herpes Simplex Encephalitis; Autoimmune Encephalitis; Anti-NMDAR Antibodies